Okręg Tarnopol Armii Krajowej .......... 195 - Dudek, Tomasz (Kresowi żołnierze Armii Krajowej: Historia – Polityka – Pamięć, 2024)
THE HOME ARMY TARNOPOL DISTRICTThis section discusses the history of the ZWZ-AK (The Home Army Union of Armed Struggle) in its Tarnopol district during World War Two. In this paper, the author attempted to showcase the operations of individual units of the Polish underground resistance organisation in the Tarnopol area which targeted the Soviets, the Germans, and the Ukrainians, as well as to reconstruct the staffing of the Tarnopol district structures. The author did not ignore an important, yet little known issue of the Polish civilian self-defence organised against Ukrainian nationalists targeting the Polish population with criminal acts in the Tarnopol area. It was the Polish self-defence operatives who allowed large clusters of Polish population to survive. In the final part of the section, the author discussed the course of Operation Tempest and attempted to reconstruct the underground resistance structures under the new occupational force, the Soviets. The structures concerned are both the “NIE” resistance organisation and the extra-territorial Tarnopol district of the WIN (Freedom and Independence Association) formed in the novel environment of the Recovered Territories (a.k.a. Regained Lands or Western Borderlands).